Technologies for HIV prevention and care: challenges for health services - Ivia Maksud; Nilo Martinez Fernandes; Sandra Lucia Filgueiras (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
ABSTRACTThis article aims to consider some relevant challenges to the provision of "new prevention technologies" in health services in a scenario where the "advances" in the global response to AIDS control are visible. We take as material for analysis the information currently available on the HIV post-exposure prophylaxis (PEP) and pre-exposure prophylaxis (PrEP), treatment as prevention (TASP) and over the counter. The methodology consisted of the survey and analysis of the Biblioteca Virtual em Saúde (BVS: MEDLINE, LILACS, WHOLIS, PAHO, SciELO) articles that addressed the issue of HIV prevention and care in the context of so-called new prevention technologies. The results of the studies show that there is assistance on the ground of clinics for the treatment of disease responses, but there are several challenges related to the sphere of prevention. The articles list some challenges regarding to management, organization of services and the attention given by health professionals to users. The current context shows evidence of the effectiveness of antiretroviral therapy in reducing the risk of HIV transmission, but the challenges for the provision of preventive technologies in health services permeate health professionals and users in their individual dimensions and health services in organizational and structural dimension. Interventions should be made available in a context of community mobilization; there should be no pressure on people to make HIV testing, antiretroviral treatment or for prevention. In the management is responsible for the training of health professionals to inform, clarify and make available to users, partners and family information about the new antiretroviral use strategies.